Long Term Survivals in Aggressive Primary Brain Malignancies Treated With an Adjuvant Ketogenic Diet - Schwartz, Kenneth A.; Noel, Mary; Nikolai, Michele; Olson, Lawrence K.; Hord, Norman G.; Zakem, Micheal; Clark, Justin; Elnabtity, Mohamed; Figueroa, Bryan; Chang, Howard T. (Frontiers in Nutrition, 2022)
Aggressive primary brain tumors (APBT) glioblastoma multiforme and grade IV astrocytoma are treated with multimodality treatments that include surgery to remove as much tumor as possible without sacrificing neurological function followed by radiation therapy and chemotherapy usually temozolomide. Survivals in adults are in the range of 8-16 months. The addition of a ketogenic diet (KD) to rodents with transplanted brain tumors increased survival in 9 of 11 animals to over 299 days compared to survival in untreated controls of 33 days and radiation only controls of 38 days. We treated humans with APBT with standard of care neurosurgery immediately followed by 6 weeks of an adjuvant ketogenic diet concurrent with radiation therapy and temozolomide. Twice daily measurements of blood ketones and glucose were recorded and the patients’ diet was modified towards the goal of maintaining blood ketone levels approaching 3 mM. Of the 9 patients who completed the protocol 3 younger patients age 32, 28 and 22 at enrollment are alive and employed with clinically stable disease and brain images 74, 58 and 52 months since diagnosis. All the 6 older patients mean age 55 have died with disease progression detected on average 8 months after Dx. In conclusion: 1. It is possible to implement and maintain dietary induced ketosis in patients with APBT; 2. The longer survivals observed in younger patients treated with KD need to be confirmed in larger studies that should be focused on younger patients possibly under age 40. Clinical Trials registered (NCT01535911)